Pengaruh Capital Intensity dan Transfer Pricing Terhadap Tax Avoidance dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Uniyati, Uniyati; Sirait, Iren Meita (JURNAL ONLINE INSAN AKUNTAN, 2025)
A The aim of this research is to know and analyze the effect of capital intensity and transfer pricing on tax avoidance and determine the influence of company size in moderating the relationship between capital intensity and tax avoidance, and determine the influence of company size in moderating the relationship between transfer pricing and tax avoidance. This research is an associative study, with a population of property and real estate sector listed on the Indonesia Stock Exchange in the 2019-2022 period. The sampling method in this research is purposive sampling. The analysis technique uses panel data regression analysis and the MRA (Moderated Regression Analysis) test. The results of this research show that the capital intensity and transfer pricing variables have no effect on tax avoidance. The variable company size cannot moderate the relationship between capital intensity and tax avoidance, and company size cannot moderate the relationship between transfer pricing and tax avoidance .   Keywords : Capital Intensity, Transfer Pricing, Tax Avoidance, Company Size